Intraarterial urokinase for thrombus migration after mechanical thrombectomy for large vessel ischemic stroke. Issue 1 (February 2023) - Neki, Hiroaki; Katano, Takehiro; Maeda, Takuma; Shibata, Aoto; Komine, Hiroyuki; Kikkawa, Yuichiro
Background: Achieving rapid and complete reperfusion is the ultimate purpose for ischemic stroke with large vessel occlusion (LVO). Although mechanical thrombectomy (MT) had been a proverbially important procedure, medium vessel occlusion (MeVO) with thrombus migration can sporadically occur after MT. Moreover, the safe and effective approach for such had been unknown. We reported thrombolysis with intraarterial urokinase for MeVO with thrombus migration after MT. Methods: We included 122 patients who were treated by MT with LVO stroke at our institution between April 2019 and March 2021. Of 26 patients (21.3%) who developed MeVO with thrombus migration after MT, 11 (9.0%) underwent additional MT (MT group) and 15 (12.3%) received intraarterial urokinase (UK group). The procedure time; angiographically modified Treatment in Cerebral Ischemia Scale (mTICI); functional independence, which was defined as modified Rankin Scale 0–2, on day 30 or upon discharge; and symptomatic and asymptomatic intracerebral hemorrhage (ICH) were compared between the UK and MT groups. Results: The procedure time, mTICI, and asymptomatic ICH did not significantly differ between the groups. In the UK group, 8 of 15 (53.3%) patients obtained functional independence, and the functional independence rate was significantly higher in the UK group than in the MT group ( p < 0.05). Symptomatic ICH did not occur in the UK group, and its incidence was significantly smaller than that in the MT group ( p < 0.05). Conclusion: The results of this study suggest that intraarterial urokinase for MeVO with thrombus migration after MT may safely improve angiographic reperfusion.